Effects of humic acids from different sources on sodium and micronutrient levels in corn plants - Horuz, Ayhan (Penerbit Universiti Kebangsaan Malaysia, 2020)
The use of activated humic acids (HAs) in agricultural applications is a relatively recent development. Corn (Zea mays L.) is a major food and silage crop in Turkey and yields are reduced in calcareous soils by sodium (Na) toxicity and carbonate (CO3 ) induced deficiencies of some micronutrients. In this study, the effects of two HAs extracted using the wet-alkali technique and activated with nitrogen (N2 ) and oxygen (O2 ) gases, on the Na and micronutrient (iron (Fe), manganese (Mn), zinc (Zn), copper (Cu) and boron (B)) concentrations in the homogenised stems and leaves of corn plants were investigated. The experiment was conducted with a completely randomized design with factorial arrangement (2 HA types × 2 fertilisation regimes × 5 HA concentrations), with three repetitions, in a calcareous soil in pots in a greenhouse. The humic acid was applied at 100, 200, 400, and 800 mg/kg of soil before sowing the corn seed. The variance analysis showed that increasing HA levels decreased the Na concentration in the corn plants. The lowest plant Na concentrations were obtained with the addition of HA activated with N2 and O2 to both the fertilised and unfertilised treatments. The highest Zn and Cu uptakes, and Fe, Mn, and B uptakes, were associated with wet alkali extraction and gas activation, respectively. Overall, HA extracted with N2 /O2 was more effective under unfertilised conditions and wet extracted HA was more effective under fertilised conditions.